Local Hölder Regularity of Weak Solutions for Singular Parabolic Systems of p-Laplacian Type - Khoirunisa, Khoirunisa; Karim, Corina; Muslikh, M.; Mohamad Muslikh (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2021)
In this paper, the Hölder regularity of weak solutions for singular parabolic systems of p-Laplacian type is investigated. By the Poincare inequality, we show that its weak solutions within Hölder space.